2018
DOI: 10.1177/1469066718813728
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and lipidomic analysis of mammoth bone by high-resolution tandem mass spectrometry coupled with liquid chromatography

Abstract: Investigation of archeological and paleontological artifacts at the molecular level has become a trend over the recent years. Paleogenomics provides information about the evolution of ancient species; paleoproteomics was recently established as branch of conventional proteomics dedicated to the study of proteomes of extinct organisms. At the same time paleolipidomics, which could focus on the investigation of lipids of ancient species, is not developed yet, though the investigation of fossil lipids may have po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…In gel electrophoresis, Tuross (1989) detected three different protein bands, for one band she supposed the presence of albumin because of the similar molecular weight. Other related investigations on Pleistocene mammals were published recently (e.g., Cappellini et al 2012;Hill et al 2015;Kostyukevich et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gel electrophoresis, Tuross (1989) detected three different protein bands, for one band she supposed the presence of albumin because of the similar molecular weight. Other related investigations on Pleistocene mammals were published recently (e.g., Cappellini et al 2012;Hill et al 2015;Kostyukevich et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly Schweitzer and her group (Schweitzer et al 2013), who was very active and successful during the last 15 years, sequenced protein fragments from bone collagen of a 100,000 to 600,000-year-old mastodon and a 68-millionyear-old dinosaur (Asara et al 2007). However, also other groups identified non-collagenous ECM proteins such as osteonectin and osteopontin in 120 ky Pleistocene mammals using mass spectrometry (Cappellini et al 2012;Hill et al 2015;Kostyukevich et al 2018), while Kostyukevich and colleagues also detected with coupled liquid chromatography lipids (Kostyukevich et al 2018). Also impressive is the work of Cappellini and his group dealing with tandem mass spectrometry which enables the sequencing of collagen type 1 from a 1.5-million-year-old sample of a tooth from Cretaceous fossil remains (Cappellini et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lipids also undergo NonP taphonomic alteration processes. For example, fatty acids are rapidly hydrolyzed from the glycerol unit in phospholipid and glyceride diagenesis (Briggs et al 2000;Kostyukevich et al 2018;Nolan et al 2020); the resultant fatty acids can then be hydroxylated or methylated, among other NonP taphonomic alterations (Stefanova & Disnar 2000). While NonP taphonomically altered lipids and sterols often serve as biomarkers within sedimentary organic matter (Briggs & Summons 2014;Mackenzie et al 1982;Mackenzie et al 1981;O'Reilly et al 2017;Philp & Gilbert 1987), such biomarkers have not often been reported within vertebrates prior to the Neogene (Briggs et al 2000;O'Reilly et al 2017).…”
Section: B Non-polymerizing Taphonomic Alterationmentioning
confidence: 99%
“…Unaltered phospholipids and glycerides are rapidly hydrolyzed post-mortem, releasing their constituent fatty acids from glycerol (Briggs et al 2000;Kreps et al 1981;Schoenen & Schoenen 2013). Intact phospholipids are generally not recovered even from permafrost frozen Pleistocene soft tissues (Kostyukevich et al 2018;Kreps et al 1981). Unbound, saturated fatty acids, on the other hand, can be recovered from permafrost specimens (Kostyukevich et al 2018;Kreps et al 1981).…”
Section: Biomolecule and Biomarker Preservationmentioning
confidence: 99%
See 1 more Smart Citation